Aggregation is a critical cause of poor transfer into the brain tissue of intravenously administered cationic PAMAM dendrimer nanoparticles - Kurokawa Y (Dove Medical Press, 2017)
Yoshika Kurokawa,1 Hideko Sone,1 Tin-Tin Win-Shwe,1 Yang Zeng,1 Hiroyuki Kimura,2 Yosuke Koyama,1 Yusuke Yagi,2 Yasuto Matsui,3 Masashi Yamazaki,4 Seishiro Hirano1 1Center for Health and Environmental Risk Research, National Institute for Environmental Studies, Tsukuba, Ibaraki, 2Department of Analytical and Bioinorganic Chemistry, Kyoto Pharmaceutical University, 3Department of Environmental Engineering, Kyoto University Graduate School of Engineering, Kyoto, 4TIA Center Office, National Institute of Advanced Industrial Science and Technology, Tsukuba, Ibaraki, Japan Abstract: Dendrimers have been expected as excellent nanodevices for brain medication. An amine-terminated polyamidoamine dendrimer (PD), an unmodified plain type of PD, has the obvious disadvantage of cytotoxicity, but still serves as an attractive molecule because it easily adheres to the cell surface, facilitating easy cellular uptake. Single-photon emission computed tomographic imaging of a mouse following intravenous injection of a radiolabeled PD failed to reveal any signal in the intracranial region. Furthermore, examination of the permeability of PD particles across the blood–brain barrier (BBB) in vitro using a commercially available kit revealed poor permeability of the nanoparticles, which was suppressed by an inhibitor of caveolae-mediated endocytosis, but not by an inhibitor of macropinocytosis. Physicochemical analysis of the PD revealed that cationic PDs are likely to aggregate promptly upon mixing with body fluids and that this prompt aggregation is probably driven by non-Derjaguin–Landau–Verwey–Overbeek attractive forces originating from the surrounding divalent ions. Atomic force microscopy observation of a freshly cleaved mica plate soaked in dendrimer suspension (culture media) confirmed prompt aggregation. Our study revealed poor transfer of intravenously administered cationic PDs into the intracranial nervous tissue, and the results of our analysis suggested that this was largely attributable to the reduced BBB permeability arising from the propensity of the particles to promptly aggregate upon mixing with body fluids. Keywords: PAMAM dendrimer, nanomaterial, aggregation, blood–brain barrier